PENINGKATAN HASIL BELAJAR SOAL CERITA TENTANG DEBIT DENGAN STRATEGI POLYA DI SD - Parisna, Domita (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study was conducted in two cycles, with the first cycle consisted of two meetings and the second cycle consisted of one meeting. Judging from the results obtained by the student in the learning of each cycle, the first cycle shows the average value, student learning outcomes (cognitive, affective and psychomotor) was 62%. While there was an increase in the second cycle is excellent, where the value obtained mastery learning has reached 76%. Kata unci; soal cerita tentang debit; strategi polya